Synovitis in knee osteoarthritis assessed by contrast-enhanced magnetic resonance imaging (MRI) is associated with radiographic tibiofemoral osteoarthritis and MRI-detected widespread cartilage damage: the MOST study - Guermazi, Ali; Hayashi, Daichi; Roemer, Frank; Zhu, Yanyan; Niu, Jingbo; Crema, Michel D.; Javaid, M. Kassim; Marra, Monica D.; Lynch, John A.; El-Khoury, George Y.; Zhang, Yuqing; Nevitt, Michael C.; et al. (Journal of Rheumatology, 2014)
To examine the cross-sectional association of whole-knee synovitis assessed by contrast-enhanced magnetic resonance imaging (CEMRI) with radiographic tibiofemoral osteoarthritis (OA), non-CEMRI-assessed cartilage damage, and meniscal status.Multicenter Osteoarthritis Study (MOST) is a cohort study of people with or at high risk of knee OA. Subjects are a subset of MOST who volunteered for both CEMRI and non-CEMRI. Using CEMRI, synovitis was assessed at 11 sites and graded 0-2 at each site. Presence of "whole-knee synovitis" was defined as the synovitis score of >= 1 at any site from each knee. Cartilage and meniscal damage was evaluated using non-CEMRI based on the Whole Organ MRI Score. Logistic regression was used to assess associations of synovitis with radiographic OA (Kellgren-Lawrence grade >= 2), widespread cartilage damage, and meniscal damage, adjusting for age, sex, and body mass index (BMI). Additional analyses were performed excluding subjects who had chondrocalcinosis on radiography and those taking antiinflammatory medications.Four hundred four subjects were included (mean age 58.8 ± 7.0 yrs, BMI 29.6 ± 4.9 kg/m(2), 45.5% women). On CEMRI, the maximum synovitis score across 11 sites in each knee was 0 in 106 knees (26.2%), 1 in 135 (33.4%), and 2 in 163 (40.4%). Synovitis was associated with radiographic OA [adjusted OR (aOR) 3.25, 95% CI 1.98-5.35] and widespread cartilage damage (aOR 1.91, 95% CI 1.24-2.92). Severe meniscal damage showed a borderline significant association with synovitis (aOR 1.74, 95% CI 0.99-3.04). Additional analyses as described did not notably change the results.CEMRI-detected synovitis is strongly associated with tibiofemoral radiographic OA and MRI-detected widespread cartilage damage.
EVALuna2:14548